Influence of fungicides on the elements of structure and crop productivity of grain triticale of winter variety Dynamo - Bushtewich, Victor N.; Pazniak, Elena I.; Dashkevitch, Michail A.; Petrenko, Natalia M.; Bondarchuk, Valentina A. (Journal of the Belarusian State University. Ecology, 2018)
The results of studies on the effect of various fungicides on the productivity of the triticale of the winter strain Dynamo are presented. It was found that the use of fungicides contributed to a reduction in the development of diseases and increased the density of productive stems by 12,2–12,8 %, the number of grains in the ear is 3,7 to 11,4 %, the weight of 1000 grains is 2,6 to 7,8 %. This ensured an increase in yield by 8,8–15,1 %. These indicators were the highest when using 31 tilt turbo (1,0 l / ha), DK 41 amistar trio (0,75 l / ha), DK 60 menar 90,5 l / ha) in the DC stage.
Keywords: winter triticale; fungicides; powdery mildew; grain yield; elements of the crop structure; the number of productive stems; the number of grains in the ear; the mass of 1000 grains